2011
DOI: 10.1016/j.ajpath.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pea3 Group Transcription Factors in Esophageal Squamous Cell Carcinoma

Abstract: The transcription factors Pea3, Erm, and Er81 can promote cancer initiation and progression in various types of solid tumors. However, their role in esophageal squamous cell carcinoma (ESCC) has not been elucidated. In this study, we found that the expression levels of Pea3 and Erm, but not that of Er81, were significantly higher in ESCC compared with nontumor esophageal epithelium. A high level of Pea3 expression was significantly correlated with a shorter overall survival in a cohort of 81 patients with ESCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…16, 28, 29, 30 Moreover, it was previously shown that CCAR2 regulates breast and colon cancer progression by acting respectively as PEA3 and PROX-1 transcription factors co-activator 7, 17 and, of note also these proteins are implicated in AKT pathway regulation. 31, 32 …”
Section: Discussionmentioning
confidence: 99%
“…16, 28, 29, 30 Moreover, it was previously shown that CCAR2 regulates breast and colon cancer progression by acting respectively as PEA3 and PROX-1 transcription factors co-activator 7, 17 and, of note also these proteins are implicated in AKT pathway regulation. 31, 32 …”
Section: Discussionmentioning
confidence: 99%
“…Among them, ETV4, a member of the Ets family of transcription factors, was notable for both its correlation with SOX2 in primary SCCs and its previously reported role in SCC pathogenesis (35). ETV4 has also been reported to be overexpressed in airway basal cells (31), thus linking it to a SOX2-p63-positive cell population.…”
Section: Figurementioning
confidence: 99%
“…Likewise, ETV4 and ETV1 are overexpressed in esophageal adenocarcinomas and may cooperate with activated MAPKs in stimulating proliferation and invasion of OE33 esophageal squamous cancer cells [162]. Another report posits that ETV4 and ETV5, but not ETV1, are overexpressed in esophageal squamous cell carcinomas and that ETV4 expression correlates with a shorter overall survival [163]. Also, ETV4 is upregulated in ovarian tumors and its expression correlated with reduced survival [41,164].…”
Section: Role In Other Cancersmentioning
confidence: 99%